Light harvesting in purple bacteria does not rely on resonance fine-tuning in peripheral antenna complexes - Keil, Erika; Lokstein, Heiko; Cogdell, Richard; Hauer, Jürgen; Zigmantas, Donatas; Thyrhaug, Erling (Photosynthesis research, 2024)
The ring-like peripheral light-harvesting complex 2 (LH2) expressed by many phototrophic purple bacteria is a popular model system in biological light-harvesting research due to its robustness, small size, and known crystal structure. Furthermore, the availability of structural variants with distinct electronic structures and optical properties has made this group of light harvesters an attractive testing ground for studies of structure-function relationships in biological systems. LH2 is one of several pigment-protein complexes for which a link between functionality and effects such as excitonic coherence and vibronic coupling has been proposed. While a direct connection has not yet been demonstrated, many such interactions are highly sensitive to resonance conditions, and a dependence of intra-complex dynamics on detailed electronic structure might be expected. To gauge the sensitivity of energy-level structure and relaxation dynamics to naturally occurring structural changes, we compare the photo-induced dynamics in two structurally distinct LH2 variants. Using polarization-controlled 2D electronic spectroscopy at cryogenic temperatures, we directly access information on dynamic and static disorder in the complexes. The simultaneous optimal spectral and temporal resolution of these experiments further allows us to characterize the ultrafast energy relaxation, including exciton transport within the complexes. Despite the variations in PPC molecular structure manifesting as clear differences in electronic structure and disorder, the energy-transport and-relaxation dynamics remain remarkably similar. This indicates that the light-harvesting functionality of purple bacteria within a single LH2 complex is highly robust to structural perturbations and likely does not rely on finely tuned electronic- or electron-vibrational resonance conditions.
Keywords: Bacterial Proteins; Rhodopseudomonas; světlo; světlosběrné proteinové komplexy; Energy transfer; Energy Transfer; Light-Harvesting Protein Complexes; bakteriální proteiny; Light; Ultrafast spectroscopy; Excitons; Light-harvesting; přenos energie